Atezolizumab plus bevacizumab versus lenvatinib for unresectable hepatocellular carcinoma: a large real-life worldwide population. (February 2023) - Casadei-Gardini, Andrea; Rimini, Margherita; Tada, Toshifumi; Suda, Goki; Shimose, Shigeo; Kudo, Masatoshi; Cheon, Jaekyung; Finkelmeier, Fabian; Lim, Ho Yeong; Rimassa, Lorenza; Presa, José; Masi, Gianluca; et al.
Abstract: Background and aims: Atezolizumab plus bevacizumab and lenvatinib have not been compared in a randomised controlled trial. We conducted a retrospective multi-centre study to compare the clinical efficacy and safety of lenvatinib and atezolizumab with bevacizumab as a first-line treatment for patients with unresectable HCC in the real-world scenario. Methods: Clinical features of lenvatinib and atezolizumab plus bevacizumab patients were balanced through inverse probability of treatment weighting (IPTW) methodology, which weights patients' characteristics and measured outcomes of each patient in both treatment arms. Overall survival (OS) was the primary end-point. Results: The analysis included 1341 patients who received lenvatinib, and 864 patients who received atezolizumab plus bevacizumab. After IPTW adjustment, atezolizumab plus bevacizumab did not show a survival advantage over lenvatinib HR 0.97 (p = 0.739). OS was prolonged by atezolizumab plus bevacizumab over lenvatinib in viral patients (HR: 0.76; p = 0.024). Conversely, OS was prolonged by lenvatinib in patients with non-alcoholic steatohepatitis/non-alcoholic fatty liver disease (HR: 1.88; p = 0.014). In the IPTW-adjusted population, atezolizumab plus bevacizumab provided better safety profile for most of the recorded adverse events. Conclusion: Our study did not identify any meaningful difference in OS between atezolizumab plus bevacizumab and lenvatinib. Although some hints are provided suggesting that patients with non-alcoholic steatohepatitis/non-alcoholic fatty liver disease might benefit more from lenvatinib therapy and patients with viral aetiology more from atezolizumab plus bevacizumab. Highlights: No randomised trial has been conducted to compare atezolizumab plus bevacizumab to lenvatinib. Atezolizumab plus bevacizumab did not show a survival advantage over lenvatinib. Lenvatinib provided longer in patients with NASH/NAFLD. Atezolizumab plus bevacizumab provided longer in patients with viral aetiology. Atezolizumab plus bevacizumab consistently reduced any toxicity and those graded as 3–4.